1998
DOI: 10.1111/j.1572-0241.1998.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

The utility of endoscopy in the management of patients with gastroesophageal reflux symptoms

Abstract: Most patients undergoing endoscopy for symptoms of GERD were switched to omeprazole regardless of the endoscopic findings. No esophageal cancer was identified and the incidence of Barrett's esophagus was low. It appears that endoscopy itself did not change the management of patients receiving H2-blocker therapy. A trial of a proton pump inhibitor before endoscopy should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…In a large survey, almost 20% of the endoscopied patients had a normal appearing mucosa and, furthermore, no malignant lesions were found in these subjects, who most likely had had symptoms of GER for long periods of time (14). In a recent Finnish study, only 15% of the patients under 50 years of age were found to have mucosal changes in endoscopy (15).…”
Section: Discussionmentioning
confidence: 97%
“…In a large survey, almost 20% of the endoscopied patients had a normal appearing mucosa and, furthermore, no malignant lesions were found in these subjects, who most likely had had symptoms of GER for long periods of time (14). In a recent Finnish study, only 15% of the patients under 50 years of age were found to have mucosal changes in endoscopy (15).…”
Section: Discussionmentioning
confidence: 97%
“…In our hospital referral area with approximately 250,000 inhabitants, 10 esophageal and 50 gastric cancers are detected yearly. In a recent study with 742 GERD patients, the prevalence of Barrett’s esophagus was 6.3%, but none had esophageal cancer [42]. Moreover, in patients aged <55 years, virtually all patients with gastric or esophageal cancer have sinister symptoms (weight loss, dysphagia, persistent vomiting) when cancer is diagnosed [43].…”
Section: Discussionmentioning
confidence: 99%
“…No consensus exists on its precise role or on when it is best performed. 15 16 The use of endoscopy will depend on local cost, accessibility, and timing relative to treatment. Most patients should be managed empirically, at least initially.…”
Section: When Should Patients Be Referred For Endoscopy?mentioning
confidence: 99%